Evaluation of formulation design on the physical and structural properties of commercial cream cheeses. (23rd July 2022) - Kim, Jiuk; Watkinson, Philip; Matia‐Merino, Lara; Smith, Jeremy R.; Golding, Matt
Summary: This study investigated how the compositional properties and formulation design of commercial cream cheese products model cheese influenced physical and structural properties as compared to a model cheese composition. Of the seven products evaluated, three were block format (B), two were spreadable (S) and two were spreadable light (SL), with fat contents ranging from 13.7 to 35.7%. The majority of cream cheese products indicated the inclusion of starter culture, and all formulations contained one or more stabilisers. Protein/moisture (p/m) ratio, i.e. the effective protein concentration in the non‐fat substance, was seen to most strongly correlate with material properties, with a positive slope for fracture stress (R 2 = 0.808) and modulus of deformability (R 2 = 0.721). In terms of outliers, the datapoint for SL2 on this modulus versus p/m graph was lower than its regression line, and one rationale is that lower fat content (13.7%) gave a lower modulus from the milkfat component at 10°C test temperature. B1, with the highest p/m of 0.17, had a more dense distribution of larger fat globules coated with proteins than B2 and B3. Fracture stress and modulus of deformability were noted to be higher for full‐fat than for lower fat cheese. In all products, elastic characteristics dominated viscous flow as expected. Findings have demonstrated that significant variance exists across the material properties of commerical cream cheeses, and which shows specific dependencies on their formulation. Abstract : Compositional variance and cream cheeses and impact on functional and structural properties.